2021
DOI: 10.34117/bjdv7n8-022
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of CalB Lipase by adsorption on magnetic nanoparticles: A heterogeneous biocatalysis/ Imobilização da lipase CalB por adsorção em nanopartículas magnéticas: um biocatalisador heterogêneo

Abstract: Iron magnetic nanoparticles (Fe3O4) were evaluated as adsorption preparative heterofunctional support for the immobilization of lipase B from Candida antarctica (CALB). Heterogeneous magnetic catalysts are easy to recover by the magnetic field, which may optimize operational cost and enhance the purity of the products. The nanoparticles were produced by the co-precipitation method. Modifications were carried out on the nanoparticles' surfaces with aminopropyltriethoxysilane (APTS). The adsorption was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Candida antarctica lipase B (CaLB) has been also immobilized on hetero-functional MNPs by numerous methods, such as (i) adsorption on aminopropyltrimethoxysilane (ApTMOS)modified MNPs for kinetic resolution (KR) of secondary alcohols [39], on Lys-modified MNPs [40], on gallic acid-formaldehyde grafted MNPs [41], (ii) affinity binding of Histagged CaLB on magnetite MNPs containing long-armed nickel-nitrilotriacetic acid surface groups [42], or by (iii) covalent binding using diazonium chemistry for immobilization on carbon-coated MNPs [43], epoxy functionalized polymer-grafted MNPs [44], or (after glutaraldehyde activation) onto chitosan-coated MNPs [45,46], onto ApTMOS-activated MNPs [47][48][49][50], onto Lys-modified MNPs [40], and (iv) a combination of covalent attachment and polymer embedding onto MNPs [51]. The above-mentioned CaLB-MNP biocatalysts were already applied to produce short-and medium-chain fatty esters, employed as taste components [52], flavor esters [50,51,53], biodiesel [54], or to perform kinetic resolution of racemic secondary alcohols [39,46]. It was also shown that ultrasound agitation improves CaLB-MNPs activity [52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida antarctica lipase B (CaLB) has been also immobilized on hetero-functional MNPs by numerous methods, such as (i) adsorption on aminopropyltrimethoxysilane (ApTMOS)modified MNPs for kinetic resolution (KR) of secondary alcohols [39], on Lys-modified MNPs [40], on gallic acid-formaldehyde grafted MNPs [41], (ii) affinity binding of Histagged CaLB on magnetite MNPs containing long-armed nickel-nitrilotriacetic acid surface groups [42], or by (iii) covalent binding using diazonium chemistry for immobilization on carbon-coated MNPs [43], epoxy functionalized polymer-grafted MNPs [44], or (after glutaraldehyde activation) onto chitosan-coated MNPs [45,46], onto ApTMOS-activated MNPs [47][48][49][50], onto Lys-modified MNPs [40], and (iv) a combination of covalent attachment and polymer embedding onto MNPs [51]. The above-mentioned CaLB-MNP biocatalysts were already applied to produce short-and medium-chain fatty esters, employed as taste components [52], flavor esters [50,51,53], biodiesel [54], or to perform kinetic resolution of racemic secondary alcohols [39,46]. It was also shown that ultrasound agitation improves CaLB-MNPs activity [52].…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned CaLB-MNP biocatalysts were already applied to produce short-and medium-chain fatty esters, employed as taste components [52], flavor esters [50,51,53], biodiesel [54], or to perform kinetic resolution of racemic secondary alcohols [39,46]. It was also shown that ultrasound agitation improves CaLB-MNPs activity [52].…”
Section: Introductionmentioning
confidence: 99%